2016
DOI: 10.1038/srep28602
|View full text |Cite
|
Sign up to set email alerts
|

Paternal overweight is associated with increased breast cancer risk in daughters in a mouse model

Abstract: While many studies have shown that maternal weight and nutrition in pregnancy affects offspring’s breast cancer risk, no studies have investigated the impact of paternal body weight on daughters’ risk of this disease. Here, we show that diet-induced paternal overweight around the time of conception can epigenetically reprogram father’s germ-line and modulate their daughters’ birth weight and likelihood of developing breast cancer, using a mouse model. Increased body weight was associated with changes in the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 64 publications
2
58
0
Order By: Relevance
“…Thus, we studied the mammary cancer risk in control and LP daughters using a well-established [5, 27] carcinogen-induced mouse model of breast cancer. Tumor latency was significantly shorter in LP daughters compared with controls ( P  = 0.029; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we studied the mammary cancer risk in control and LP daughters using a well-established [5, 27] carcinogen-induced mouse model of breast cancer. Tumor latency was significantly shorter in LP daughters compared with controls ( P  = 0.029; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, paternal factors also play a role in the offspring’s birthweight [14]. In line with this, we recently reported that paternal high-fat diet intake or overweight leads to increased birthweight, alterations in mammary gland development, and higher rates of breast cancer risk in daughters in two rodent models [5, 6]. While no studies in humans have directly investigated the link between paternal nutrition and breast cancer in daughters, an association between other paternal factors and cancer risk in the progeny has been reported [1517].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…We previously reported that paternal consumption of obesity-inducing diets (OID) at the pre-243 conception window increased female offspring's susceptibility to breast cancer [15,16]. In those 244 studies, we also described mammary gland morphological changes as well as metabolic 245 dysfunction-a phenotype also reported by others-in offspring of obese fathers [16,18,19,32].…”
Section: Offspring Of Oid Fathers Have Impaired Metabolic Function Anmentioning
confidence: 79%
“…However, a role for paternal exposures in 67 modulating breast cancer predisposition in offspring has emerged in recent years. We recently 68 showed that paternal obesity, malnutrition and consumption of a high-fat diet all lead to 69 increased breast cancer development in offspring [15][16][17], a phenotype associated with changes 70 in normal mammary gland development. We also found that a recurrent phenotype 71 accompanying offspring's cancer predisposition is metabolic dysfunction [16][17][18], raising the 72 possibility that paternally-induced cancer development could be a function of both systemic 73 effects as well as tissue specific changes.…”
Section: Introduction 52mentioning
confidence: 99%